Depression by inbreeding after four sucessive self-pollination squash generations - Cardoso, AII (Universidade de São Paulo (USP), 2004)
The strategy for breeding F-1 hybrid squash is to develop parental lines through self-pollination. However, it increases plant mean homozygosis, which is not the natural genetic state of a cross-pollinated species, and can cause inbreeding depression. The objective of this work was to evaluate this depression with sucessive generations of self-pollination (without selection) in Cucurbita moschata, cv. Piramoita. Populations were obtained from lines with one to four generations of self-pollination (obtained by the SSD method), from the original cv. Piramoita (population SO). Randomized blocks were used with five treatments (different generations of self-pollination -S-0 to S-4), six replicates and five plants per plot. Regression analysis was made by the Wright inbreeding coefficient (F) to measure the homozygosis level effect on vigor loss. There was a linear reduction of mean weight and fruit length, seed production (number and weight) per fruit with the increase of the homozygosis level; however inbreeding did not affect seed quality (weight of 100 seeds and germination).
Keywords: Cucurbita moschata; cucurbits; selfing